Determination of thermal accommodation coefficients on CaSiO3 and SiO2 using molecular dynamics and experiments. (February 2022) - Bayer-Buhr, D.; Vimal, M.; Prakash, A.; Gross, U.; Fieback, T.
Highlights: First Measurements on highly porous CaSiO3 insulation material. Thermal accommodation coefficient of CaSiO3-Ar/N2 close to 1 due to adsorption phenomena. No significant influence of temperature on TAC at temperature differences smaller than 50 K. Molecular dynamics simulation showed lower values due to missing physical adsorption as in experiments. Abstract: The thermal accommodation coefficient α has been assumed, although lacking any experimental proof, to be near unity for most gases so far, which denotes no influence. However, it plays a contributing role in the field of the effective thermal conductivity of highly porous insulation materials based on S i O 2 or C a S i O 3 as it is shown in this work. Besides, this work investigates a possible influence on α for A r, N 2, H e within parameters like temperature, roughness and contamination as this has not been examined on such materials so far. More importantly, it answers the question whether the assumption of α = 1 is valid. By using a parallel plates device, very similar to the guarded-hot-plate, following EN 12667 it was possible to determine α on a dense C a S i O 3 . It occured that the assumptions α = 1 (for A r, N 2 ) and α = 0.3 (for H e ) are valid for measurements near room temperature. Further, physical adsorption was found to increase α . The determination of the influence of roughness has been started showing an interesting effect, but it still remains an open topic. In a collaborative study molecular dynamics (MD) simulations were performed showing a strong equivalence of α between S i O 2 and C a S i O 3 . These results can be considered a lower limit of α as neither roughness nor adsorption processes have been included in the simulation. Therefore, any deviations between experiments and MD could be considered as an apperance of physical adsorption.